ANALISIS SEMIOTIKA PESAN DAKWAH DALAM WEB SERIES USTADZ MILLENIAL - Fitri Meliya Sari (SOURCE : Jurnal Ilmu Komunikasi, 2022)
The Web Series “Ustadz Millenial” tells the story of a life that tells the story of the life of a young man who aspires to become a young ustadz. However, his family's troubles and death are his dreams. But he still tries to realize his ideals by preaching through social media. Based on the background above, the purpose of this study is to answer how the signified and the signifier as well as the object (referent) are displayed in the series "Ustadz Millenial" and what are the da'wah messages contained in the series "Ustadz Millenial". In its analysis, this study uses a qualitative approach with the semiotic method of Ferdinand de Saussure which focuses on the signifier and the signified as well as the object (referrent). The data studied are pieces of images, text, sounds, or sounds contained in the series "Ustadz Millenial". The results of the study show that the "Millenial Ustadz" series is full of da'wah messages, including; an invitation to use patience, forgive each other, maintain friendship, try and endeavor, keep fifteen, be devoted to both parents, preach through social media that is developing with technology in today's era, and display the hijab as a suggestion to cover the genitals.